2018
DOI: 10.1186/s40463-018-0266-y
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal recurrence sites in patients previously treated with transoral laser microsurgery for squamous cell carcinoma

Abstract: BackgroundThe laryngeal framework provides a natural barrier preventing tumour spread to extralaryngeal structures. Transoral laser microsurgery (TLM) for laryngeal squamous cell carcinoma (SCC) may violate these boundaries, altering the pathways of tumor spread for potential recurrences. Our project objective is to describe laryngeal SCC recurrence patterns and overall survival in patients requiring total laryngectomy (TL) after TLM.MethodsPatients undergoing TLM for laryngeal SCC requiring salvage TL were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…22 In this view, CO 2 TOLMS should be regarded as a repeatable procedure, and patients should be carefully monitored according to dedicated protocols, including seriate biologic endoscopic and radiologic examinations, [23][24][25] to avoid late diagnosis of recurrence/metachronous tumor in the presence of laryngeal framework involvement. 26 Our data confirm that CO 2 TOLMS, with adequate indications and patient selection, provides optimal oncologic results as a salvage procedure after previous transoral laser surgery, as already demonstrated by our group in the clinical setting of failure after RT. 27,28 In recurrent cases not manageable by CO 2 TOLMS, it should be considered that OPHL, although associated with lower OP, resulted in a better DSS than RT.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…22 In this view, CO 2 TOLMS should be regarded as a repeatable procedure, and patients should be carefully monitored according to dedicated protocols, including seriate biologic endoscopic and radiologic examinations, [23][24][25] to avoid late diagnosis of recurrence/metachronous tumor in the presence of laryngeal framework involvement. 26 Our data confirm that CO 2 TOLMS, with adequate indications and patient selection, provides optimal oncologic results as a salvage procedure after previous transoral laser surgery, as already demonstrated by our group in the clinical setting of failure after RT. 27,28 In recurrent cases not manageable by CO 2 TOLMS, it should be considered that OPHL, although associated with lower OP, resulted in a better DSS than RT.…”
Section: Discussionsupporting
confidence: 87%
“…These results confirm the importance of treating EIGSCC with a single‐treatment modality, 21 avoiding RT in case of persistence, recurrence, or second tumor still amenable to CO 2 TOLMS 22 . In this view, CO 2 TOLMS should be regarded as a repeatable procedure, and patients should be carefully monitored according to dedicated protocols, including seriate biologic endoscopic and radiologic examinations, 23–25 to avoid late diagnosis of recurrence/metachronous tumor in the presence of laryngeal framework involvement 26 . Our data confirm that CO 2 TOLMS, with adequate indications and patient selection, provides optimal oncologic results as a salvage procedure after previous transoral laser surgery, as already demonstrated by our group in the clinical setting of failure after RT 27 , 28 .…”
Section: Discussionsupporting
confidence: 62%
“…1 According to a study by Horwich et al, TLM does not result in a lower rate of locoregional control and overall survival of patients after total laryngectomy. 16 As per a study by Ahmed et al, KTP assisted TLM results in good functional outcomes. 1 It has been reported that for early lesions of the glottis, single modality treatment in the form of radiation or surgery offers comparable voice outcomes.…”
Section: Discussionmentioning
confidence: 81%
“…A type V cordectomy may compromise the connective tissue barriers within the larynx, such as the conus elasticus, quadrangular membrane, ventricular connective tissue, and Broyles' ligament (commissural tendon) (16). Recurrent tumors could spread from the glottis to the supra/subglottis and paraglottic space, which have a more abundant lymph node basin (17).…”
Section: Discussionmentioning
confidence: 99%